Fighting the illusion of control: How to make use of cue competition and alternative explanations - Vadillo, Miguel; Universidad de Deusto (Pontificia Universidad Javeriana, 2012)
Misperceptions of causality are at the heart of superstitious thinking and pseudoscience. The main goal of the present work is to show how our knowledge about the mechanisms involved in causal induction can be used to hinder the development of these beliefs. Available evidence shows that people sometimes perceive causal relationships that do not really exist. We suggest this might be partly due to their failing to take into account alternative factors that might be playing an important causal role. The present experiment shows that providing accurate and difficult-to-ignore information about other candidate causes can be a good strategy for reducing misattributions of causality, such as illusions of control.